2012
DOI: 10.1007/s10870-012-0319-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of 5-Amino-1-nitriminotetrazole and Its Salts

Abstract: New nitrogen-rich energetic compound 5-amino-1-nitriminotetrazole (2) and its ammonium (3), hydrazinium (4) salts have been prepared. Their structures were characterized and confirmed by 1 H NMR spectroscopy, IR spectroscopy, elemental analysis and ESI-MS, X-ray single-crystal diffraction. Compound 2 crystallizes in the orthorhombic Pna2(1) space group with unit cell parameters are a = 9.229 (2) Å , b = 5.5271 (13) Å , c = 10.295(2) Å , V = 525.1(2) Å 3 , Z = 4. Compound 3 crystallizes in the Monoclinic C2/c s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…12 Additionally, Li et al found that a mixture of fuming nitric acid and concentrated sulfuric acid (98%) could be a suitable nitration agent to obtain 5-amino-1-nitrimino-4H-tetrazole. 13 In recent years, Christe successfully synthesized and characterized several novel polynitrogen cations, such as the V-shaped N 5 + cation, 14 the N 3 NOF + cation both as a Z-and E-isomers, 15 and the N 7 O + cation. 16 All the catenated nitrogen cations were obtained by the substitution reaction of [N-F] + with HN 3 to replace the F atom by an azido …”
Section: Scheme 2 Extending the Nitrogen Chain By N-aminationmentioning
confidence: 99%
“…12 Additionally, Li et al found that a mixture of fuming nitric acid and concentrated sulfuric acid (98%) could be a suitable nitration agent to obtain 5-amino-1-nitrimino-4H-tetrazole. 13 In recent years, Christe successfully synthesized and characterized several novel polynitrogen cations, such as the V-shaped N 5 + cation, 14 the N 3 NOF + cation both as a Z-and E-isomers, 15 and the N 7 O + cation. 16 All the catenated nitrogen cations were obtained by the substitution reaction of [N-F] + with HN 3 to replace the F atom by an azido …”
Section: Scheme 2 Extending the Nitrogen Chain By N-aminationmentioning
confidence: 99%
“…[1] Thec ombination of both aspects yields very powerful energetics.T he known nitramino tetrazoles without alkyl chains [2] are limited to the examples shown in Scheme 1. [3,4] Thes ynthesis of 1,s hown in Scheme 2, starts with commercially available dimethylcarbonate,w hich is treated with hydrazine hydrate to give the methyl carbazate (2). Thes ynthesis of this compound has been al ong-term goal in energetic materials research because of its outstanding predicted performance.T o date,many attempts of direct nitration have failed.…”
mentioning
confidence: 99%
“…Thes ynthesis of this compound has been al ong-term goal in energetic materials research because of its outstanding predicted performance.T o date,many attempts of direct nitration have failed. [3,4] Thes ynthesis of 1,s hown in Scheme 2, starts with commercially available dimethylcarbonate,w hich is treated with hydrazine hydrate to give the methyl carbazate (2). Species 2 is reacted with cyanogen azide to yield Nmethoxycarbonyl protected 1,5-diaminotetrazole (3), which is then nitrated in acetonitrile with N 2 O 5 .T he nitramide 4 is decomposed in solution with aqueous KOHt og ive 5 as aw hite precipitate from which 1 can be isolated by acidification and extraction into organic solvents.…”
mentioning
confidence: 99%
“…They play roles as ligands to form energetic complexes [7][8][9][10][11][12][13][14][15] or as anions to construct energetic salts together with guanidine, amine, etc. [16][17][18][19][20][21][22]. 1,5-Diaminotetrazole (DAT) is one of the highest nitrogen content (84.0 wt%) compounds and is shown in figure 1.…”
Section: Introductionmentioning
confidence: 99%